Constraining star formation timescales with molecular gas and young star clusters. Issue Volume 15:Issue S352(2019) (June 2019) - Grasha, Kathryn; Calzetti, Daniela
Abstract: Star formation provides insight into the physical processes that govern the transformation of gas into stars. A key missing piece in a predictive theory of star formation is the link between scales of individual stars and star clusters up to entire galaxies. LEGUS is now providing the information to test the overall organization and spatial evolution of star formation. We present our latest findings of using star clusters from LEGUS combined with ALMA CO observations to investigate the transition from molecular gas to star formation in local galaxies. This work paves the way for future JWST observations of the embedded phase of star formation, the last missing ingredient to connect young star clusters and their relation with gas reservoirs. Multi-wavelength studies of local galaxies and their stellar and gas components will help shed light on early phases of galaxy evolution and properties of the ISM at high-z.